The Influence of Motivation, Ethics, and Work Environment on Employee Performance at CV. Surya Food Indonesia Blitar - Engelien Yusniar Permanasari; Soebiantoro Soebiantoro (Jurnal Manajemen Bisnis Era Digital, 2025)
The role of human resources in a company is crucial and must be utilized as effectively as possible. To achieve this, it is necessary to implement strategies that motivate employees to work willingly and apply their skills and competencies to achieve optimal performance. Employee performance is influenced by several factors, including motivation, ethics, and the work environment. This study employed a saturated sampling technique, meaning that the entire population of 93 employees at CV. Surya Food Indonesia Blitar was used as the sample. Data were collected through questionnaires and documentation methods. The results of the analysis revealed that motivation significantly influences employee performance. Similarly, ethics also has a significant impact on how employees perform their duties. Furthermore, the work environment plays a key role in shaping employee performance. Collectively, motivation, ethics, and the work environment were found to have a combined and significant effect on the performance of employees at CV. Surya Food Indonesia Blitar. These findings highlight the importance of fostering a motivated, ethical, and supportive workplace to enhance overall productivity.